Portrait of a Young Painter - Vaughan, Mary Kay (Duke University Press, 2021)
This book adopts a biographical approach to understanding the culture surrounding the Mexico City youth rebellion of the 1960s. Mary Kay Vaughan's chronicle of the life of painter Pepe Zúñiga counters a literature that portrays post-1940 Mexican history as a series of uprisings against state repression, injustice, and social neglect that culminated in the student protests of 1968. Rendering Zúñiga's coming of age on the margins of formal politics, Vaughan depicts midcentury Mexico City as a culture of growing prosperity, state largesse, and a vibrant, transnationally-informed public life that produced a multifaceted youth movement brimming with creativity and criticism of convention. By discussing the influences that shaped Zuniga's worldview, she historicizes the process of subject formation and shows how doing so offers new perspectives on the events of 1968.